2013
DOI: 10.1182/blood-2013-02-485888
|View full text |Cite|
|
Sign up to set email alerts
|

Three-year efficacy, safety, and survival findings from COMFORT-II, a phase 3 study comparing ruxolitinib with best available therapy for myelofibrosis

Abstract: Key Points• Long-term analysis of the COMFORT-II Trial shows that ruxolitinib treatment results in durable reductions in splenomegaly and is well tolerated.• Patients randomized to ruxolitinib showed longer overall survival than those receiving the BAT.Ruxolitinib is a potent Janus kinase (JAK)1/JAK2 inhibitor that has demonstrated rapid reductions in splenomegaly and marked improvement in disease-related symptoms and quality of life in patients with myelofibrosis (MF). The present analysis reports the 3-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
369
1
12

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(400 citation statements)
references
References 14 publications
18
369
1
12
Order By: Relevance
“…[14][15][16] Splenomegaly is not included in established prognostic scoring systems for MF but data from ruxolitinib-based clinical trials have demonstrated an adverse prognostic impact of the initial spleen volume and the lack of spleen volume reduction on treatment. [17][18][19] In MF, these associations were only established because the spleen volume was accurately measured by volumetry through computer tomography (CT) or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Splenomegaly is not included in established prognostic scoring systems for MF but data from ruxolitinib-based clinical trials have demonstrated an adverse prognostic impact of the initial spleen volume and the lack of spleen volume reduction on treatment. [17][18][19] In MF, these associations were only established because the spleen volume was accurately measured by volumetry through computer tomography (CT) or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term outcome of ruxolitinib therapy in MF was recently reported and disclosed a very high treatment discontinuation rate (92% after a median time of 9.2 months) and the occurrence of severe withdrawal symptoms during ruxolitinib treatment discontinuation ("ruxolitinib withdrawal syndrome") characterized by acute relapse of disease symptoms, accelerated splenomegaly, worsening of cytopenias and occasional hemodynamic decompensation, including a septic shock-like syndrome [140]. The 3-year follow-up information on the companysponsored phase 3 study disclosed a 55% drug discontinuation rate and a slight but significant improvement in survival [141]. Furthermore, several reports have now associated ruxolitinib with serious opportunistic infections [122].…”
Section: Th Anniversary Issuementioning
confidence: 99%
“…The JAK1‐2 inhibitor ruxolitinib is a potent anti‐inflammatory agent and has shown promising results in the treatment of patients with MF3, 4, 5 and PV6 in regard to reducing splenomegaly, constitutional symptoms, and inflammation‐mediated comorbidities. However, in the large majority of patients, ruxolitinib does not markedly reduce the JAK2 V617F allele burden (%V617F) 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…However, in the large majority of patients, ruxolitinib does not markedly reduce the JAK2 V617F allele burden (%V617F) 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%